Om at udfordre den svenske exceptionalisme - At undervise som sort - Habel, Ylva (K&K - Kultur og Klasse, 2015)
Sweden imagines itself as a race-less, tolerant country, purportedly less affected by postcolonial relations than other nations, by virtue of its welfare politics, and its democratic, egalitarian principles. This national self-image, which is situated within a regional discursive framework of Nordic exceptionalism, has been contested by intersectional, postcolonial, critical race and whiteness studies; yet there is a widespread conviction that Sweden has had no real part in the imperial adventure, and therefore remains untouched by colonial and postcolonial social dynamics. These persistent claims to political innocence are often forcefully reproduced as three forms of positioning: sanctioned ignorance, normative colorblindness, and white liberal doubt. Working as a Black scholar and teacher within a postcolonial curriculum in this context involves several challenges. The article adresses the pedagogical challenges I face as a Black film and media studies scholar in pedagogical situations where I teach predominantly white students about media representations of the African Diaspora. Taking my point of departure in Swedish everyday discourse that negates the significance of race, my article visualizes some of the obstacles and challenges that I encounter in teaching situations on predominantly postcolonial courses. While working to encourage students to let go of sanctioned ignorance about racial issues, one of my greatest challenges has been to make them unlearn the colorblindness that has long been a cherished part of Swedish identity.